The challenges of using high-throughput sequencing to track multiple bipartite mycoviruses of wild orchid-fungus partnerships over consecutive years - Dixon, Kingsley (Reed Elsevier, 2017)
The bipartite alpha- and betapartitiviruses are recorded from a wide range of fungi and plants. Using a combination of dsRNA-enrichment, high-throughput shotgun sequencing and informatics, we report the occurrence of multiple new partitiviruses associated with mycorrhizal Ceratobasidium fungi, themselves symbiotically associated with a small wild population of Pterostylis sanguinea orchids in Australia, over two consecutive years. Twenty-one partial or near-complete sequences representing 16 definitive alpha- and betapartitivirus species, and further possible species, were detected from two fungal isolates. The majority of partitiviruses occurred in fungal isolates from both years. Two of the partitiviruses represent phylogenetically divergent forms of Alphapartitivirus, suggesting that they may have evolved under long geographical isolation there. We address the challenge of pairing the two genomic segments of partitiviruses to identify species when multiple partitiviruses co-infect a single host.